Effects of human footprint and biophysical factors on the body‐size structure of fished marine species. Issue 2 (27th July 2021) - Bosch, Nestor E.; Monk, Jacquomo; Goetze, Jordan; Wilson, Shaun; Babcock, Russell C.; Barrett, Neville; Clough, Jock; Currey‐Randall, Leanne M.; Fairclough, David V.; Fisher, Rebecca; Gibbons, Brooke A.; Harasti, David; et al.
Abstract: Marine fisheries in coastal ecosystems in many areas of the world have historically removed large‐bodied individuals, potentially impairing ecosystem functioning and the long‐term sustainability of fish populations. Reporting on size‐based indicators that link to food‐web structure can contribute to ecosystem‐based management, but the application of these indicators over large (cross‐ecosystem) geographical scales has been limited to either fisheries‐dependent catch data or diver‐based methods restricted to shallow waters (<20 m) that can misrepresent the abundance of large‐bodied fished species. We obtained data on the body‐size structure of 82 recreationally or commercially targeted marine demersal teleosts from 2904 deployments of baited remote underwater stereo‐video (stereo‐BRUV). Sampling was at up to 50 m depth and covered approximately 10, 000 km of the continental shelf of Australia. Seascape relief, water depth, and human gravity (i.e., a proxy of human impacts) were the strongest predictors of the probability of occurrence of large fishes and the abundance of fishes above the minimum legal size of capture. No‐take marine reserves had a positive effect on the abundance of fishes above legal size, although the effect varied across species groups. In contrast, sublegal fishes were best predicted by gradients in sea surface temperature (mean and variance). In areas of low human impact, large fishes were about three times more likely to be encountered and fishes of legal size were approximately five times more abundant. For conspicuous species groups with contrasting habitat, environmental, and biogeographic affinities, abundance of legal‐size fishes typically declined as human impact increased. Our large‐scale quantitative analyses highlight the combined importance of seascape complexity, regions with low human footprint, and no‐take marine reserves in protecting large‐bodied fishes across a broad range of species and ecosystem configurations. Resumen: Las pesquerías marinas de los ecosistemas costeros en muchas áreas del mundo históricamente han removido a individuos de gran tamaño, potencialmente perjudicando el funcionamiento ambiental y la sostenibilidad a largo plazo de las poblaciones de peces. Los reportes sobre los indicadores basados en el tamaño que se vinculan con la estructura de la red alimenticia pueden contribuir al manejo basado en el ecosistema, aunque la aplicación de estos indicadores a grandes (inter‐ecosistemas) escalas geográficas ha estado limitada a datos de captura dependientes de las pesquerías o métodos basados en el buceo restringidos a aguas someras (<20 m), lo cual puede representar erróneamente la abundancia de peces de gran tamaño capturados para la pesca. Obtuvimos los datos de la estructura del tamaño corporal de 82 teleósteos marinos demersales focalizados por razones recreativas o comerciales tomados de 2, 904 despliegues de video estéreo subacuático remoto con cebo (stereo‐BRUV, en inglés). El muestreo se realizó hasta los 50 metros de profundidad y abarcó aproximadamente 10, 000 km del talud continental de Australia. El relieve marino, la profundidad del agua y la gravedad humana (es decir, un indicador de los impactos humanos) fueron los pronosticadores más sólidos de la probabilidad de incidencia de los peces de gran tamaño y de la abundancia de peces por encima del tamaño legal mínimo de captura. Las reservas marinas de protección total tienen un efecto positivo sobre la abundancia de los peces que están por encima del tamaño legal, aunque el efecto varió según el grupo de especies. Como contraste, los peces de tamaño sublegal fueron pronosticados de mejor manera usando gradientes de la temperatura de la superficie marina (media y varianza). En las áreas con un impacto humano reducido, los peces de gran tamaño corporal tenían hasta tres veces mayor probabilidad de aparecer y los peces de tamaño legal eran aproximadamente cinco veces más abundantes. Para los grupos de especies conspicuas con afinidades contrastantes de hábitat, ambiente y biogeografía, la abundancia de peces de tamaño legal normalmente declinó conforme aumentó el impacto humano. Nuestros análisis cuantitativos a gran escala resaltan la importancia conjunta que tienen la complejidad marina, las regiones con una huella humana reducida y las reservas marinas de protección total para la protección de los peces de gran tamaño corporal en una extensa gama de especies y configuraciones ecosistémicas. Efectos de la Huella Humana y los Factores Biofísicos sobre la Estructura del Tamaño Corporal de Especies Marinas Capturadas para la Pesca